Análise das questões de física do novo exame nacional do ensino médio - MOREIRA, Rogério de Oliveira (2024)
Due to the importance of Enem for students in the final years of elementary school, our research is on the analysis of the tests of the New National High School Exam in order to evaluate the exam questions and relate them to the recommendations and guidance of content for high school. For this it is necessary to identify the characteristics of the tests, relate the questions by area of knowledge of physics and within those areas the most charged subjects, select the most important contents and how they are charged. Initially, we made a study of the characteristics of the PCN for High School and ENEM correlating the structuring themes with the reference matrix along with the textbook proposals and then we analyzed the 10 tests from 2009 to 2018 in order to raise their characteristics. From this research it is verified that the tests are contextualized and with conceptual questions, there remains a predominance of the areas of electricity and mechanics and finally runs away from the old traditional entrance exams. Thus, we find that Enem is in resonance with the High School recommendations.